Novice teachers' perceptions of the use of rehearsals to support their learning of ambitious mathematics teaching. Issue 4 (7th August 2020) - Rawlins, Peter; Anthony, Glenda; Averill, Robin; Drake, Michael
ABSTRACT: While there is a broad evidence base about what constitutes effective mathematics teaching in schools, less is known about how to effectively prepare novice teachers to teach in these ways. This article reports on a project designed to support novice teachers to become "ambitious" mathematics teachers by utilising practice-based approaches involving cycles of rehearsals and in-the-moment coaching. Acknowledging the important role that student voice has in curriculum reforms, we sought novice teachers' perceptions about the introduction of rehearsal activities. Novice teachers' support for rehearsals for developing their mathematical pedagogical skills is presented alongside implications for instructional reforms within mathematics methods courses.